LinguaComp como ferramenta no ensino-aprendizagem de línguas: uma proposta para desenvolvimento da habilidade de produção escrita em língua inglesa - Maquiné, Gilmara Oliveira (2020)
The use of Information and Communication Technologies has been growing and strengthening in the educational field, based on the evolution and continuous improvement of these resources. Thereby, different digital technologies have been developed that are used as facilitators in the teaching-learning process. In this context, we present a computational tool, called LinguaComp, developed to support the application of a proposal to develop and evaluate the written production in English. The proposal include three phases: Orientation, Textualization and Self-review, based on the text creation model of Domínguez García (2006). The methodological process involve research with a qualitative approach, made possible through a case study (YIN, 2015). The instruments used for data collection were questionnaires used during the initial survey and assessment of the LinguaComp. The proposal was applied and evaluated through the use of LinguaComp, with 26 students from the technical course of integrated middle level in Chemistry, from the Federal Institute of Education, Science and Technology of Amazonas (IFAM), in the English language. The tool was evaluated based on ergonomic aspects of interaction / man-machine (usability, interoperability, documentation), using a questionnaire with five-point of Likert Scale. The results showed that the tool helped in the process of assessment the ability of written production, generating artifacts that facilitate and speed up the evaluation, such as a computational environment for sending tasks online; an interface for evaluating written production, through a rubric; the possibility of generating data referring to self-assessment carried out by students; space for sending textual feedbacks to students; general monitoring reports, with quantitative datas (notes) expanded by individual graphs that indicate the performance of students in the evaluated criteria. In addition to these contributions, the results also demonstrate elements of usability identified in the assessment of the tool, such as the indication of consistency and standards in the nomenclature used in the buttons and menus, minimizing the memory load of the participants when using the tool, as well as the effectiveness of messages of success and error. Through this research, two educational products were generated, a computational tool, based on the web (LinguaComp) and a manual, with guidelines for the use of this tool in the teaching, learning process and, mainly, evaluation of the performance achieved in the scope of didactics of languages.